Single nucleotide polymorphisms: A paradigm in oral disease research - Ummer, Hiba; Santosh, Arvind Babu Rajendra; Surboyo, Meircurius Dwi Condro; Chitipothu, Mani Deepthi; Sivanandham, Shamala (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: A higher occurrence of oral cancer is observed in South Asian and Southeast Asian countries when compared with other countries in the world. Cancer, a disease with complex pathophysiology, has been linked to chronic inflammation. Inflammation has been considered an important component of tumor initiation and progression. This is supported by the fact that many cancers arise at the sites of chronic inflammation, but the exact mechanism by which inflammation influences cancer is unknown. Purpose: This review article correlates single nucleotide polymorphisms (SNPs), chronic inflammation, and oral cancer. The article emphasizes the critical role that SNPs play in oral cancer susceptibility, progression, and prognosis. This involves discussing the impact of specific SNPs on oral cancer risk and patient outcomes. Review: Gene polymorphism has been documented in the molecular pathogenesis of various cancers, including oral cancer, and SNPs are the most common form of gene polymorphism. Genetic variation has been documented in the molecular pathogenesis of various cancers, including oral cancer, and SNPs are the most common form of gene polymorphism. SNPs have been documented in inflammatory conditions as well as in various diseases. Conclusion: SNPs have phenotypic consequences and therefore can serve as genetic fingerprints. The upregulation or downregulation of genes is able to drive oral carcinogenesis.